USE OF CONJUGATIONS IN KARLUK DIALECTS OF SAMARKAND REGION (TAMADDUN NURI JURNALI, 2024)
This article focuses on information about the origin of the karluk language and dialect. Opinions were expressed about the dialects of the karluk region of Samarkand region and the agreements in the Uzbek literary language, their interchangeability. Conjunctions used in dialects and their meeting forms in the language of ancient written monuments are discussed.